PENGARUH KEPEMILIKAN MANAJERIAL, FREE CASH FLOW DAN INVESTMENT OPPORTUNITY SET TERHADAP DPR - Fadhilaturrochmah, Ayu; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine the influence of managerial ownership, free cash flow, and investment opportunity set to the dividend payout ratio through annual financial statement which has been prepared by automotive companies which are listed in Indonesia Stock Exchange. The independent variables of this research are managerial ownership, free cash flow and investment opportunity set whereas the dependent variable is dividend payout ratio. This research is quantitativeand the research population is automotive companies which are listed in Indonesia Stock Exchange (IDX) in 2011-2015 periods. The research samplesare 12 automotive companies which has been selected by using purposive sampling technique. The data analysis technique has been carried out by using multiple linear regressions analysis. The result of the research shows that managerial ownership and free cash flow give influence to the dividend payout ratio whereas investment opportunity set does not give any influence to the dividend payout ratio.Keywords: Managerial Ownership, Free Cash Flow, Investment Opportunity Set, Dividend Payout Ratio.